Enzootic bovine leukosis (EBL) – bibliographic review - Guntzel, Maria Eduarda; Griebeler, Neide Maria (JRG Journal of Academic Studies, 2023)
The present study aims to demonstrate the forms of contagion and development of LEB, as well as to present control and prevention measures and to present the two clinical conditions of the disease related to cattle. Bovine Enzootic Leukosis (LEB) mainly affects cattle causing a drop in production that results in economic loss for the producer. This disease is caused by a deltaretrovirus, which has immunosuppressive potential with a chronic course. This virus has tumor RNA that acts on the lymphoid system, causing disorganization of the tissues and organs of the animal, the most affected are the lymph nodes that end up losing their primary characteristics and are replaced by a new tissue of neoplastic nature that form lymphosarcomas, this process can cause a leukemic process. Therefore, the general objective of this work is to show producers the importance of having knowledge about this infectious and contagious disease that causes significant economic losses to cattle breeding.